Synthesis and Antibacterial Activity of 6-Subsituted phenyl-4-)2'-hydroxy-4'-ethoxy-5'-H/Nitro/bromo phen-1'-yl-2,3,4,5-tetrahydropyrimidine-2-thione - M. Barot, Vijay; Naik, H.B. (Asian Journal of Chemistry, 2010)
Abstract is not available.